Kinerja UMKM Kecamatan Kesambi terkait Pengaruh Literasi dan Inklusi Keuangan - Siswanto, Deny Hadi (PELITA JURNAL PENELITIAN DAN KARYA ILMIAH, 2024)
The aim of this research is to find out in depth the influence of financial literacy and inclusion on the performance of MSMEs in Kesambi District. This research uses quantitative methods by collecting data through questionnaires distributed to 100 MSMEs in the area. The sampling technique used in this research is probability sampling and saturated sampling, which allows the entire MSME population in Kesambi District to have the same opportunity to be selected as respondents. To analyze the collected data, the multiple linear regression method was used to see the relationship between financial literacy and inclusion and the performance of MSMEs in a comprehensive manner. The research results show that financial literacy and financial inclusion have a significant influence on the performance of MSMEs. Increasing financial literacy and better access to formal financial services can directly improve the performance of MSMEs in the region, with a positive impact on business growth and financial stability of MSME players. This research emphasizes the importance of financial factors in the success of small and medium enterprises, and highlights the need to increase understanding and utilization of financial services among MSME entrepreneurs. These results also underline the important role of financial inclusion in creating more equitable and sustainable economic opportunities for MSMEs in Kesambi District